Perlindungan Hukum terhadap Anak yang jadi Korban Prostitusi demi Mewujudkan Nilai Keadilan - Tarigan, Rudy; Idham, Idham; Erniyanti, Erniyanti (Penerbit Goodwood, 2022)
Purpose: The purpose of this study is to determine the legal protection of children who are used as prostitution according to positive law in Indonesia, and the obstacles and efforts to protect the law against children who are used as prostitution. Method: The method used is empirical juridical research, namely research through a series of field interviews with respondents and informants. Besides that, it also uses normative research, namely research through library research. Result: Legal protection for children who are used as prostitution according to positive law in Indonesia is regulated in the Child Protection Act, the Law on Trafficking in Persons and the Law on the Protection of Witnesses and Victims which includes the provision of rehabilitation, supervision, and the provision of strict sanctions against perpetrators . Obstacles to legal protection for children who are used as prostitution in Batam City are that there are no specific legal arrangements regarding child prostitution, a lack of special escort personnel for child victims of prostitution, and a lack of human resources in the field of children. Conclusion: Efforts to overcome this are utilizing existing legal provisions, increasing coordination and cooperation with agencies related to children, and maximizing the performance of existing officers.